PEMODELAN DAN PENGENDALIAN MOTOR DC TYPE DRIPPROOF-SEPARATELY VENTYLATED DENGAN TEGANGAN JANGKAR - Buang, Misbahuddin (Aliansi Dosen Perguruan Tinggi Swasta Indonesia (Adpertisi), 2023)
A dc motor is a machine that converts dc electrical energy into mechanical energy. One way to assess the work of a dc motor is to know the amount of current and speed in the initial conditions before adjustments/changes are made. Current and speed settings can be made by adjusting the motor armature voltage at starting. The greater the time the armature voltage reaches its nominal value, the armature current will be smaller so that it is safe for the motorbike and vice versa.